(untitled) (Nigerian Journal of Technology, 2023)
This study examines how melting heat transfer affects the MHD Casson nanofluid’s stagnation point when there are both homogeneous and heterogeneous chemical reactions occurring along with viscous dissipation. Additionally taken into account in this study are the effects of thermophoresis and Brownian motion. The linked non-linear partial differential equations that control nanofluid flow can be reduced to couple non-linear ordinary differential equations using local similarity variables, which can then be numerically solved using the Spectral Collocation technique, as demonstrated in the current flow mathematical modeling. Both qualitative and quantitative data are presented to show how flow control settings affect fluid flow, temperature, and nanoparticle concentration. The comparison of the current results with previously published works revealed good agreement, as shown in table 1.